A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Paciﬁc - Brown, Samuel D. J. (Zootaxa, 2019)
Proterhinus tauai Brown, new species is described from specimens collected on the island of Miti‘aro in the Cook Islands, South Paciﬁc. It differs from congeners by the combination of having a dorsal vestiture of decumbent brown clavate scales, lacking erect elongate setae, anterior pronotal angles projecting forwards, and having short antennae that do not reach the posterior margin of the pronotum. This species shows strong sexual dimorphism in the shape of the rostrum, with males having a large semicircular rostrum, compared with a stout subrectangular rostrum in females. Fitting allometric models to the relationship of morphometric variables with body length show that rostrum width and area have signiﬁcantly different allometric relationships between the sexes, consistent with hypotheses of sexual selection. Proterhinus tauai was collected from coastal scrub vegetation. Collection data and observation of captive specimens indicate a host relationship with the parasitic vine Cassytha ﬁliformis L. (Lauraceae).